1950
DOI: 10.1149/1.2777979
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanism of Sensitized Luminescence of Solids

Abstract: Reflection, excitation, and emission spectra of CaSiO3:false(normalPbfalse) and CaSiO3:false(normalPb+normalMnfalse) are reported, as well as measurements of the dependence of luminescence intensity on exciting intensity for CaSiO3:false(normalPb+normalMnfalse) and normalNaCl:false(normalPb+normalMnfalse) . It is shown that the data support the conventional concept of sensitization, where all the ultraviolet absorption is due to the sensitizer, and that Butler's picture, where the activator absorbs ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1954
1954
1983
1983

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Assuming an average value for the ratio of quantum outputs of 1.8 and a concentration of activator equal to 2.6 mole % MnCO3, the range over which energy is transferred, K, is 39 atoms. This is in agreement with experimentally determined values for other systems (4,8,9) as well as the theoretically predicted value (11).…”
Section: Sensitized Luminescencesupporting
confidence: 92%
See 1 more Smart Citation
“…Assuming an average value for the ratio of quantum outputs of 1.8 and a concentration of activator equal to 2.6 mole % MnCO3, the range over which energy is transferred, K, is 39 atoms. This is in agreement with experimentally determined values for other systems (4,8,9) as well as the theoretically predicted value (11).…”
Section: Sensitized Luminescencesupporting
confidence: 92%
“…The range of transfer of energy from sensitizer to activator may be calculated according to the relationship (4,8,9) Quantum Output Mn…”
Section: Sensitized Luminescencementioning
confidence: 99%
“…The previous observation (8) that irradiation in the 235 m~ absorption band does not excite the visible Mn ~ § emission in CaSiO~:Pb -t-Mn is explained easily by the fact that Mn crystallizes preferentially in the fl-CaSiO3 lattice (5, 6) and therefore it is necessary to excite the Pb atoms in fl-CaSiO3: Pb, which absorbs at 255 m~, but not at 235 m~.…”
Section: Discussionmentioning
confidence: 96%
“…GAMMA-RAY DOSIMETER GLASS Dosimeters, capable of measuring total gamma-ra3' .dosage from very low levels up through the lethal range, are now in volume production for the armed forces. These are made from a potassium, aluminum, phosphorus, silver, barium oxide glass (1,5).…”
Section: Reproducing Photographs In Plate or Window Glassmentioning
confidence: 99%
“…THE announcement of the first practical photosensitive glass (ß) in 1947 has been followed by development of other types of photosensitive glass, new related products, and applications. Some of these have been logical developments from the same research, and others, such as gamma-ray dosimeters developed by Schulman, Weyl et al (1,5), have resulted in answer to the requirements of work with atomic energy. This paper reviews the present status of the previously reported glasses and describes new developments.…”
mentioning
confidence: 99%